The Effect Of Profitability, Liquidity, Leverage, Company Size, And Board Of Commissioners Size On Corporate Social Responsibility (Csr) Disclosure - Samosir, Efansius Mario; Panjaitan, Delfi (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2023)
This study aims to examine the effects of profitability, liquidity, Leverage, firm size, and size of the board of commissioners on corporate social responsibility disclosure. The population of this study is all mining companies listed on the Indonesia Stock Exchange (IDX) during 2018–21. The samples were selected using a purposive sampling technique so that the total number of samples in this study was 57, consisting of 47 companies. Testing the hypothesis of this study using multiple linear regression analysis shows that the variables of profitability, liquidity, and Leverage do not affect the disclosure of corporate social responsibility. The size of the company and the size of the board of commissioners affect corporate social responsibility disclosure.